(untitled) (Al-Academy, 2025)
The current research aims to (reveal spontaneity in Abstract Expressionism and its reflections in the products of art education students), and the research was limited to the drawing products of the fourth grade, Art Education Department, for the academic year (2022-2023), and the research followed the descriptive analytical approach, and the research community consisted of (99) works. As for the research sample, it was (3) works that were chosen intentionally. The current research adopted (a content analysis form) and the tool was built from the indicators that resulted from the theoretical framework, and it was presented to a group of experts to ensure its validity. The analysis of the samples was also presented to analysts specialized in The art of drawing, and the research reached a set of results, the most important of which are: Among the automatic artistic characteristics that were embodied in breaking the expectation horizon, which appeared in the sample models (1, 2, 3), it constituted a percentage of (100%).